The Handbook of Communication Rights, Law, and Ethics - Loreto Corredoira, Ignacio Bel Mallen, Rodrigo Cetina Presuel, Loreto Corredoira, Ignacio Bel Mallen, Rodrigo Cetina Presuel (Wiley, 2021)
Discover how modern technological realities shape freedoms of expression and opinion with this comprehensive resource. The Handbook of Communication Rights, Law, and Ethics delivers an extensive review of the challenges facing modern communication rights. It offers readers an examination of the interplay between communication law and ethics and the role played by communication professionals in protecting individuals' rights to communication. Distinguished authors Loreto Corredoira, Ignacio Bel Mallén and Rodrigo Cetina Presuel walk readers through the fundamental ideas and concepts that represent universal common ground regarding communication rights. They compare communication rights theories developed in Europe, the United States, Latin America, Australia, and East Asia to describe how communication-related freedoms and rights are formulated and applied around the world. Finally, the meaning of the phrases "freedom of expression" and "freedom of the press" are examined in the context of national constitutions and international human rights instruments. The Handbook of Communication Rights, Law, and Ethics provides readers with: * A diverse, global perspective on how communication rights are protected and challenged around the world * A universal vision of communication rights that encourages dialogue rather than confrontation * A comparison of the American First Amendment of the Constitution with European communication rights theories and other legal traditions around the world * An exploration of the frontiers of communication rights concepts, terminology, jurisdiction, and territoriality Perfect for professors, graduate students, doctoral students, and postdoctoral researchers studying communication rights and freedom of expression around the world, The Handbook of Communication Rights, Law, and Ethics also belongs on the bookshelves of researchers studying issues surrounding freedom of the press in North America, Europe, and Latin America.